Democracy in the Digital Age challenges to political life in cyberspace - Wilhelm, Anthony G. (Routledge, 2000)
A fascinating and incisive treatment of a hot topic. This is a philosophical exploration of how emerging information and communication technologies are impacting on political participation in the United States.